CONTRIBUIÇÕES DA MODELAGEM MATEMÁTICA E DAS TECNOLOGIAS PARA O ENSINO DE EQUAÇÕES DIFERENCIAIS ORDINÁRIAS - Silva, Edcarlos Vasconcelos da (2015)
This dissertation presents results of a study made with major mathematics students. Its goal is to evidence Mathematical Modeling's contribution, supported by technological resources to Ordinary Differential Equations teaching when related to real world's non-mathematics problems. Differential equations' educating is still directioned by traditional stuff: launching contents and then exercises and tests lists. The proposal aims to show that, through resources like modeling and technologies, differential equations teaching can foment class' quality and, thus, knowledge - students and professors are stimulated, consequently. It is utilized as methodology the qualitative research one, including tools like questionary and participating observation. The populational data contains ten licenciature in mathematics students of a private university in Santa Maria, Rio Grande do Sul. The action that allowed analysing is a pedagogical intervention from November 2014. In this one, it is been in the application of five activities that addressed Brasil and Rio Grande Do Sul's populational evolution data, besides AIDS cases in brazilian population. All activities followed Mathematical Modeling steps indicated by references between technological resources (like Modellus® and Excel® softwares) used unrestrictedly.Results show that modeling technologies learning gets triumph. Students discussed themes, dealed with mathematisation and made differential modeling. As a consequence, it is verified that modeling and technologies afforded an interactive and challenging surrounding among motivated students.